2022
DOI: 10.1017/s1049023x22000796
|View full text |Cite
|
Sign up to set email alerts
|

Can Non-Physician Providers Use Ultrasound to Aid in Establishing Peripheral IV Access in Patients Who are Difficult to Cannulate? A Scoping Review

Abstract: Introduction: Non-physician performed point-of-care ultrasound (POCUS) is emerging as a diagnostic adjunct with the potential to enhance current practice. The scope of POCUS utility is broad and well-established in-hospital, yet limited research has occurred in the out-of-hospital environment. Many physician-based studies expound the value of POCUS in the acute setting as a therapeutic and diagnostic tool. This study utilized a scoping review methodology to map the literature pertaining to non-physician u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A recent review has provided evidence that non-physician medical personnel, such as paramedics and nurses, can attain proficiency in the placement of peripheral venous access using ultrasound guidance with relatively little training. This finding suggests that this technique is readily accessible and has the potential for widespread use [ 117 ].…”
Section: Reviewmentioning
confidence: 99%
“…A recent review has provided evidence that non-physician medical personnel, such as paramedics and nurses, can attain proficiency in the placement of peripheral venous access using ultrasound guidance with relatively little training. This finding suggests that this technique is readily accessible and has the potential for widespread use [ 117 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, a review demonstrated that non-physician medical personnel (paramedics, nurses, emergency department technicians) are able to achieve competence in ultrasound-guided peripheral venous access placement in patients with anticipated cannulation difficulties with relatively little training [62].…”
Section: Ultrasound Guidance In Difficult Peripheral Venous Accessmentioning
confidence: 99%
“…The development of Ultrasound-Guided Peripheral Intravenous (USGPIV) cannulation has improved the procedure's overall success rate in a host of different situations. [3][4][5][6][7][8] However, effective ultrasound-guided venous cannulation might also be challenged by the type of ultrasound equipment available, procedure field, knowledge of anatomy, and hand-eye coordination skills which are necessitated by training. 8 Smart glasses are a type of wearable computer that includes a small camera for live streaming.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, effective ultrasound-guided venous cannulation might also be challenged by the type of ultrasound equipment available, procedure field, knowledge of anatomy, and hand-eye coordination skills which are necessitated by training. 8 Smart glasses are a type of wearable computer that includes a small camera for live streaming. Smart glasses innovation has been deployed and examined across various clinical settings and healthcare facilities over the past ten years including PIVC and EMS settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation